2020
DOI: 10.1016/j.diabres.2020.108468
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes and COVID-19: The “lockdown effect”

Abstract: The aim of this study was to evaluate the effect the lockdown imposed during COVID-19 outbreak on the glycemic control of people with Type 1 diabetes (T1D) using Continuous (CGM) or Flash Glucose Monitoring (FGM). Materials and methods: We retrospectively analyzed glucose reading obtained by FGM or CGM in T1D subjects. Sensor data from 2 weeks before the lockdown (Period 0, P 0), 2 weeks immediately after the lockdown (period 1, P 1), in mid-lockdown (Period 2, P 2) and immediately after end of lockdown (Perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
71
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 12 publications
9
71
1
Order By: Relevance
“…Specifically, their time out-of-range has decreased since schools were closed in the spring of 2020, suggesting the stay-at-home protocol actually provided a better opportunity for the children to stay in range. Similar data have been reported from Spain 77 and Italy 78 ; however, a study from Israel showed that glycemic metrics for children who use CGMs were similar before and after lockdown started. 79 The panel also highlighted that big data from digital health devices is only useful if you can use it to impact care.…”
Section: Section 19: International Responses To Covid-19supporting
confidence: 82%
“…Specifically, their time out-of-range has decreased since schools were closed in the spring of 2020, suggesting the stay-at-home protocol actually provided a better opportunity for the children to stay in range. Similar data have been reported from Spain 77 and Italy 78 ; however, a study from Israel showed that glycemic metrics for children who use CGMs were similar before and after lockdown started. 79 The panel also highlighted that big data from digital health devices is only useful if you can use it to impact care.…”
Section: Section 19: International Responses To Covid-19supporting
confidence: 82%
“…Insulin use also was an independent predictor associated with 2-fold higher odds of glycaemic worsening compared with use of other glucose lowering agents. This may well reflect the increased complexity of the management of this therapeutic approach, particularly for those with T2DM, since evidence currently available for patients with T1DM on continue glucose monitoring show that glycaemic control did not worsen or even improved during lockdown [1,[9][10][11][12]. The latter, however, are younger, on continuous or flash glucose monitoring and more intensively instructed how to handle multiple dose insulin therapy or even continuous subcutaneous glucose infusion.…”
Section: N°before Lockdownmentioning
confidence: 99%
“…Although such restrictions impacted the lives of all individuals, people with chronic diseases such as diabetes could have been seriously impacted by restrictions that changed routine diet and physical activity patterns, increased stress and anxiety, and reduced access to health care resources. 26 , 27 Maintaining glycemic control can be affected by all of these factors.…”
Section: Use Cases Of Rtcgm During the Covid-19 Pandemicmentioning
confidence: 99%
“…Interestingly, several recently published studies indicate people with T1D using CGM generally had improved time in range (TIR) and reduced glucose variability. [26][27][28][29][30] For example, Brener et al found CGM metrics in pediatric T1D patients were stable during lockdown in Israel. 28 The same pattern of improved glycemic control for adults with T1D using CGM was found in Spain, 26 Italy, 27,29 and the United Kingdom.…”
mentioning
confidence: 99%
See 1 more Smart Citation